Islamic psychology: parametrical issues in defining the discipline - P.T, Abdunnazar (Penerbit Universiti Kebangsaan Malaysia, 2021)
Contemporary research trends in Islamic Psychology generally characterized as it might better be referred to as ‘Islam and Psychology’ that may be due to the lack of an agreed upon definition or a theoretical model, and the research is coming from a broad array of various disciplines including psychology, theology, philosophy, history, and mental health etc. The major areas that constitute the building blocks of Islamic Psychology are such as nafs, fitra, reliance, attachment to god, rooh, action, tawheed, taqwa, jihad al-nafs, etc. However, much of the scholarship published on the Islamic concepts tends to be philosophical in nature and often somewhat unusable partly because the terminology has not been translated or operationalized into psychological nomenclature. Islamic Psychology is ideally a domain in which scholars and practitioners from a number of basic and applied disciplines are engaged including but not limited to psychologists, psychiatrists, religious studies scholars, theologians, imams, philosophers, historians, anthropologists and others and they all think about Islamic Psychology in different ways and have specialized knowledge and expertise that they can share through collaboration as these broad disciplines and sub disciplines are also a part of the paradigm. The definitional clarity is the key challenge in developing a discipline that is certainly seems to be the case with discipline of Islamic Psychology because scholarship is happening and not bound in any sort of organized or comprehensive way. This paper discusses the parametrical concerns and issues in researches in defining and developing Islamic Psychology as a discipline.